АНАЛІЗ СТІЙКОСТІ СИСТЕМИ СТАБІЛІЗАЦІЇ НАПРУГИ НА НАКОПИЧУВАЛЬНОМУ КОНДЕНСАТОРІ ТРИФАЗНОГО ПАРАЛЕЛЬНОГО АКТИВНОГО ФІЛЬТРА - Мисак, Т.В. (Інститут електродинаміки НАН України, Київ, 2023)
The object of the study is a three-phase shunt active power filter, which consists of a two-level voltage inverter, a capacitive storage device and a damping RL-link. Decomposition of the object of study according to the rate of motion of a dynamic system makes it possible to divide this system into two subsystems, interconnected by control. The influence of the dynamic characteristics of the low-pass filter, which acts as a subsystem of communication between the voltage stabilization circuit on the capacitor of the three-phase shunt active power filter and the circuits of compensating current, on the stability of the system is considered. The formation of the compensation current is carried out by forcing the introduction of sliding modes of the first order. The mathematical model of the voltage stabilization subsystem on the capacitor using the vector of the equivalent control under the assumption of the existence of a sliding mode in the formation of the compensation current was built. The analysis of the stability of the voltage stabilization system using a low-pass filter of the second order on the first approximation was performed. To do this, the characteristic equation of a closed system for which an interval characteristic polynomial was constructed, the Kharitonov theorem, and the Rauss-Hurwitz method for a family of these polynomials was used. To confirm the theoretical assumptions, a simulation model was built and the results of digital modeling were analyzed. References 9, figure 1.